Ben Shultz: capstone - Shultz, Ben, artist (Colorado State University. Libraries, 2024)
The artist's statement: In my design practice, I'm a minimalist at heart. I believe good design communicates effectively with the least amount of information necessary. At the center of my design process—and one of my favorite parts—is extensive research. I begin all design projects the same way: scrolling through articles and webpages I may never otherwise visit, jotting down notes about what initially stands out to me, and endlessly sketching out all my "bad ideas." Accepting that my first thoughts are my worst thoughts drives me to sketch quickly, sloppily, and prolifically. The thick, permanent lines of a Sharpie are my friend in the early stages, allowing me to quickly judge my ideas without getting bogged down in the details. Ultimately, my process is a constant exploration of how simplicity, thought, and the act of creation shape our experience. By focusing on what's essential, I hope to invite viewers to look beyond the surface and engage with the quiet impact of the unseen.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design